Sports Education on Student Learning Motivation Seen from the Roles Involved in Sport Education Using Handball - Riki Ramadhan; Fauzan Effendy; Alrido Putra Pratama (Indonesian Journal of Physical Education and Sport Science)
Study purpose. This research aims to test the influence of Sport Education (SE) on students' learning motivation using handball, which can also be seen from the level of student motivation according to their role while participating in learning using SE